I'd rather be a cyborg than a celebrity: Black feminism in the digital music industry - Carmichael-Murphy, Parise (Frontiers in Communication, 2024)
This essay argues that Black feminist artists in the digital music industry embrace cyborg politics to disrupt celebrity conventions in ways that draw attention to the complexity of identity and oppression. I draw attention to Black feminism as a movement for challenging intersecting oppressions, particularly for Black women, as well as a drive to celebrate Black women's contributions to the music industry. Donna Haraway's conceptualization of the 'cyborg' can offer significant insight into how artists in the digital music industry transcend boundaries of identity to renegotiate the ideas of celebrity and fame. The cyborg is a fluid being that embraces the interconnectedness and interplay between technology and the body. By embracing cyborg politics, those who occupy space in the music industry and online can resist the commodification of their bodies to machinery alone, andalone and retain their humanity in the celebrity machine.